Ответы и объяснения

  • lili89
  • почетный грамотей
2012-05-01T18:40:14+04:00

(2,61-4х)/0,03+4,6 = 90

(2,61-4х)/0,03 = 90-4,6

(2,61-4х)/0,03 = 85,4

2,61-4х = 85,4*0,03

2,61-4х = 2,56

-4х = 2,56-2,61

-4х = -0,05

х = -0,05:(-4)

х = 0,0125

Проверяем:

(2,61-4*0,0125)/0,03+4,6 = (2,61-0,05)/0,03+4,6 =  2,56/0,03+4,6 = 85,3+4,6 = =89,9=90

Ответ: 0,0125. 

 

8,36-5,36/(0,2х+0,47х)=7,56

-5,36/0,67х = 7,56-8,36

-5,36/0,67х = -0,8

0,67х = -5,36/(-0,8)

0,67х = 6,7 

х = 6,7/0,67

х = 10

Проверяем:

8,36-5,36/(0,2*10+0,47*10)= 8,36-5,36/(2+4,7)= 8,36-5,36/6,7 = 8,36-0,8 =7,56

Ответ: 10.